Poverty and sustainable development impacts of REDD architecture; options for equity growth and the environment - Nabanoga, Gorettie; Namaalwa, Justine; Ssenyonjo, Edward (International Institute for Environment and Development, 2010)
Poverty and sustainable development impacts of REDD architecture is a multi country project led by the International Institute for Environment and Development (IIED, UK) and the University of Life Sciences (Aas, Norway). It started in July 2009 and will continue to May 2013. The project is funded by the Norwegian Agency for Development Cooperation (Norad) as part of the Norwegian Government’s Climate and Forest Initiative. The first phase of the project (July 2009 to May 2010) has been in partnership with Fundação Amazonas Sustentável (Brazil); Civic Response (Ghana); SNV (Viet Nam); Sokoine University of Agriculture, Faculty of Forestry and Nature Conservation (Tanzania); and Makerere University, Faculty of Forestry and Nature Conservation (Uganda). The project aims to increase understanding of how different options for REDD design and policy at international, national and sub-national level will affect achievement of greenhouse gas emission reduction and co-benefits of sustainable development and poverty reduction. As well as examining the internal distribution and allocation of REDD payments under different design option scenarios at both international and national level, the project will work with selected REDD pilot projects in each of the five countries to generate evidence and improve understanding on the poverty impacts of REDD pilot activities, the relative merits of different types of payment mechanisms and the transaction costs.